Bolometric Light Curves of Peculiar Type II-P Supernovae. (10th March 2017) - Lusk, Jeremy A.; Baron, E.
Abstract: We examine the bolometric light curves of five Type II-P supernovae (SNe 1998A, 2000cb, 2006V, 2006au, and 2009E), which are thought to originate from blue supergiant progenitors like that of SN 1987A, using a new python package namedSuperBoL . With this code, we calculate SNe light curves using three different common techniques common from the literature: the quasi-bolometric method, which integrates the observed photometry, the direct integration method, which additionally corrects for unobserved flux in the UV and IR, and the bolometric correction method, which uses correlations between observed colors and V-band bolometric corrections. We present here the light curves calculated bySuperBoL, along with previously published light curves, as well as peak luminosities and 56 Ni yields. We find that the direct integration and bolometric correction light curves largely agree with previously published light curves, but with what we believe to be more robust error calculations, with 0.2 ≲ δ L bol / L bol ≲ 0.5 . Peak luminosities and 56 Ni masses are similarly comparable to previous work. SN 2000cb remains an unusual member of this sub-group, owing to the faster rise and flatter plateau than the other supernovae in the sample. Initial comparisons with the NLTE atmosphere codePHOENIX show that the direct integration technique reproduces the luminosity of a model supernova spectrum to ∼5% when given synthetic photometry of the spectrum as input. Our code is publicly available. The ability to produce bolometric light curves from observed sets of broadband light curves should be helpful in the interpretation of other types of supernovae, particularly those that are not well characterized, such as extremely luminous supernovae and faint fast objects.